An Enzymatic Platform for the Highly Enantioselective and Stereodivergent Construction of Cyclopropyl‐δ‐lactones. (17th September 2020) - Ren, Xinkun; Liu, Ningyu; Chandgude, Ajay L.; Fasan, Rudi
Abstract: Abiological enzymes offers new opportunities for sustainable chemistry. Herein, we report the development of biological catalysts derived from sperm whale myoglobin that exploit a carbene transfer mechanism for the asymmetric synthesis of cyclopropane‐fused‐δ‐lactones, which are key structural motifs found in many biologically active natural products. While hemin, wild‐type myoglobin, and other hemoproteins are unable to catalyze this reaction, the myoglobin scaffold could be remodeled by protein engineering to permit the intramolecular cyclopropanation of a broad spectrum of homoallylic diazoacetate substrates in high yields and with up to 99 % enantiomeric excess. Via an alternate evolutionary trajectory, a stereodivergent biocatalyst was also obtained for affording mirror‐image forms of the desired bicyclic products. In combination with whole‐cell transformations, the myoglobin‐based biocatalyst was used for the asymmetric construction of a cyclopropyl‐δ‐lactone scaffold at a gram scale, which could be further elaborated to furnish a variety of enantiopure trisubstituted cyclopropanes. Abstract : A biocatalytic strategy for the stereodivergent synthesis of cyclopropyl‐δ‐lactones via the intramolecular cyclopropanation of homoallylic diazoacetates is reported. Myoglobin was re‐engineered into two enantiocomplementary biocatalysts capable of producing a range of aryl‐ and alkyl‐substituted cyclopropane‐fused δ‐lactone scaffolds useful for medicinal chemistry and natural product synthesis.